Pendidikan dan Pelatihan Energi Baru Terbarukan (EBT) di Tingkat Universitas di Indonesia - Bledug Kusuma prasaja M; Wahyu Edifikar; Toyib Abdullah (Universitas Islam Lamongan, 2020)
The rapid increase in student enrollment at the tertiary level in Indonesia in recent years is expected to continue to increase. It is very important for universities to update their educational curricula according to the needs of the latest technology. In the current era, it is very important to include courses that cover the domains of technology, resources, design, implementation, economics, policy and application of the Renewable Energy (RE) system. Currently there is no solid foundation in various universities to provide education and training on new and renewable energy and its long-term benefits. The role of the internet is very vital in education and training in renewable energy. This paper presents the importance of delivering renewable energy education to students at the university level in Indonesia.